Chloroplast genome sequencing and divergence analysis of 18 Pyrus species: insights into intron length polymorphisms and evolutionary processes - Kim, Jung Sun; Chung, Hoyong; Park, Bohyeon; Veerappan, Karpagam; Kim, Yoon-Kyung (Frontiers in Genetics, 2024)
Pears, an essential temperate crop, are primarily produced through interspecific hybridization due to their self-incompatibility, which complicates their breeding history. To address this, we sequenced the complete chloroplast (cp) genomes of 18 Pyrus species and 1 Malus species using the Illumina HiSeq4000 platform. The cp genomes, which ranged from 159,885 to 160,153 bp, exhibited a conserved circular DNA structure with an average GC content of 36.5%. Each cp genome contained 127 genes, including 83 protein-coding genes, 36 tRNA genes, and 8 rRNA genes. Divergence analysis with mVISTA showed high conservation in coding regions and notable variation in non-coding regions. All species shared 17 intron-containing genes, with ycf3 and clpP each having two introns. Five introncontaining genes (ndhB, rpl2, rps12, trnA-UGC, and trnE-UUC) were located in IR regions, while trnL-UAA was in the LSC region, with conserved intron lengths across Pomoideae. We identified polymorphic intron sequences in rpl22, petB, clpP, ndhA, and rps16, and designed primers for these regions. Notably, the two Pyrus ussuriensis accessions, Doonggeullebae and Cheongdangrori, showed intron length polymorphisms despite being classified as the same species. Phylogenetic analysis of cp genome sequences revealed two major clusters, indicating distinct maternal lineages and evolutionary origins. This study underscores the importance of cp gene polymorphisms in P. fauriei, P. calleryana, P. ussuriensis, and P. pyrifolia, providing valuable insights into Pyrus evolution and aiding in the conservation and breeding of pear germplasm.